Apprenticeship, Vocational Training and Early Labor Market Outcomes - in East and West Germany - Regina T. Riphahn; Michael Zibrowius (Center for Economic Studies and ifo Institute (CESifo), 2015)
We study the returns to apprenticeship and vocational training for three early labor market outcomes all measured at age 25 for East and West German youths: non-employment (i.e., unemployment or out of the labor force), permanent fulltime employment, and wages. We find strong positive effects of apprenticeship and vocational training. There are no significant differences for different types of vocational training, minor differences between East and West Germany and males and females, and no significant changes in the returns over time. Instrumental variable estimations confirm the regression results. The positive returns hold up even in poor labor market situations.
Keywords: J40; J24; I29; 330; youth unemployment; school-to-work transition; returns to education; vocational training; transition economics